ID 402 – Do cortical regions encoding pain also respond to images of other's pain?. Issue 3 (March 2016) - Frot, M.; Perchet, C.; Mauguière, F.
Abstract : The aim of this study was to detect whether cortical regions encoding pain stimuli do also respond to images of other's pain using direct recordings of evoked potentials (EPs) through depth electrodes. Images depicting pain and no pain situations were presented during 100 ms, and immediately masked to thirteen patients with intracortical electrodes. Several regions were explored: insula, supra-sylvian opercular (SSop) regions, antero-medial cingulate areas (BA 24), inferior parietal cortex (BA 40), amygdala, dorso-lateral prefrontal cortex (BA 46, 9) and visual regions (V1, lingual and fusiform gyri). EPs to painful and non-painful images were averaged separately over an analysis time window of 1.5 s after the onset of image presentation. Results showed that EPs to painful and non-painful images were different in shape and amplitude especially in the posterior and anterior insulae and in the parietal part of the SSop cortex with a large negative component recorded in the painful condition. These areas were shown to be responsive to nociceptive skin Laser pain stimuli. These findings suggest that mirror pain neurons are present in these regions which might be involved in the process of human pain empathy.